EXAMPLES OF LCA METHODOLOGY IMPLEMENTATION IN STEEL INDUSTRY - A. Mitovski; D. Živković; N. Štrbac; Lj. Balanović; D. Manasijević; I. Mihajlović; Ž. Živković (Journal of Engineering & Processing Management, 2011)
Steel industry kept pace with actual trends for environmental protection in many ways - through different technological improvements considering environment protection, important share of recycling in the steel production, design of so called "eco-steels", materials designed according to recent environmental directives and legislatives, etc. In the frame of steel production monitoring, LCA methodology is very important for obtaining an accurate environmental picture of a process, due to the fact that the process should be evaluated over its entire life cycle. A number of tools and methodologies have been developed in recent years to assess the potential environmental impacts associated with a product, process or activity during its entire life cycle. The examples of Life Cycle Assessment (LCA) are used by large steel industrial companies as potentially helpful tool for improving the production processes, efficiency of resource utilization and significantly reduction of waste generation and emissions are presented in this paper.
Keywords: steel industry; Life Cycle Assessment (LCA); environmental protection